Penilaian Autentik Pada Mata Pelajaran Bahasa Indonesia di Sekolah Dasar Karesidenan Madiun - V. Teguh Suharto; Dwi Setiyadi; Nur Samsiyah; Fuad Zakiawan (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The objective of this research is to clarify the implementation of authentic assessment for Bahasa Indonesia subjects at elementary schools throughout the residency of Madiun in the last five years. This research was carried out under a qualitative-descriptive approach which applied interviews, observation, and documentation for the data collecting techniques. The results of the analysis showed that authentic assessment, in the phase of diagnostic, formative, or summative testing, was fitted to the policy of 2013 and the Merdeka Curriculum. Reasons found for it were that all types of evaluations had to be relevant with varieties of evaluation object characteristics, ie observation techniques because the evaluation objects are in the forms of observable performance and actions; paper and pencil tests were used to measure the student's'' knowledge; and interviewing was used only when something was suspicious in the students' learning process. A diagnostic test was carried out at the beginning of learning through interviews, student achievement report, and so forth.